Direct measurement of coherent phonon dynamics in solution-processed stibnite thin films - Mathews, Nripan (2014)
We report observations of coherent phonon oscillations in solution-processed polycrystalline stibnite (Sb2S3) photovoltaic thin films using transient absorption spectroscopy. Detailed optical spectroscopy correlated by extensive first-principles lattice dynamics calculations indicates that the coherent B3g longitudinal optical phonon mode with a frequency of 63.74 ± 0.05 cm−1 (or 1.911 ± 0.002 THz) at room temperature is generated via the impulsive stimulated-Raman-scattering mechanism. These strong electron-phonon interactions indicate a dominant energy-loss channel in these materials that could impose a fundamental limit on their solar energy conversion efficiency.